Assessment of the accuracy of malaria microscopy in private health facilities in Entebbe Municipality, Uganda: a cross‑sectional study - Mutabazi, Tobius; Sendaula, Emmanuel; Kakeeto, Alex; Okimat, Paul; Orishaba, Philip; Katongole, Simon Peter; Mpimbaza, Arthur; Byakika‑Kibwika, Pauline; Karamagi, Charles; Nakayaga Kalyango, Joan; Kamya, Moses R.; Dorsey, Grant; et al. (Malaria Journal, 2021)
Although microscopy remains the gold standard for malaria diagnosis, little is known about its accuracy in the private health facilities in Uganda. This study evaluated the accuracy of malaria microscopy, and factors associated with inaccurate smear results at private health facilities in Entebbe Municipality, Uganda. Methods: Between April and May 2018, all patients referred for a malaria smear in 16 private health facilities in Entebbe municipality were screened, and 321 patients were enrolled. A questionnaire was administered to collect demographic and clinical information, facility-based smear results were recorded from the participant’s consultation notes, and a research slide was obtained for expert microscopy during exit interview. A health facility assessment was conducted, and information on experience in performing malaria microscopy was collected from all facility personnel reading smears and the data was linked to the participant’s clinic visit.
Keywords: Malaria; Diagnosis; Accuracy; Microscopy; Private health facilities